Pengaruh Teknik-Teknik Audit dan Kemampuan Auditor terhadap Pelaksanaan Audit Investigatif - Aldila Sukaputri Irmadani; Shafa Audina Sukmaningrum; Nera Marinda Machdar (Jurnal Riset Ekonomi dan Akuntansi, 2024)
This research examines the influence of audit techniques and auditor abilities on the implementation of investigative audits through a literature study. Research shows that these two variables have a significant positive influence on the implementation of investigative audits. The impact of this research is the need for comprehensive auditor training regarding investigative audit techniques and developing auditors' abilities to improve the implementation of investigative audits.